Knowledge mapping of immunotherapy in castration-resistant prostate cancer: a bibliometric and visualized study (2003–2022) - Cai, Xianfu; Ding, Chenguang; Li, Yang; Zheng, Jin; Xue, Wujun (Frontiers in Urology, 2023)
Objective: To utilize bibliometric analysis to examine the literature about immunotherapy for castration-resistant prostate cancer published within the past two decades. Through this method, we aim to visualize and analyze the research progress in this field and identify the most recent trends and developments.Methods: This research conducted a comprehensive literature review on immunotherapy for castration-resistant prostate cancer. The timeframe spanned from January 2003 to December 2022, and the data was extracted from the Web of Science core collection database. The application of various software tools, such as CiteSpace, Bibliometrix, and VOSviewer, facilitated the visualization and analysis of the gathered data. These technological utilities illustrated the progression of prominent focus areas within the field.After excluding irrelevant studies, 373 papers were selected for this study. The findings suggested that the field of immunotherapy for castration-resistant prostate cancer was rapidly developing. The United States was considered to have a significant early entrant advantage in this area and profoundly influenced the field. Similarly, China's National Cancer Institute demonstrated notable